Pengembangan Idle Game “Havok Runner” Berbasis Android Menggunakan Metode Agile Game Development - Achmad Baroqah Pohan; Ibnu Alfarobi; Sofian Wira Hadi (STMIK Budi Darma, 2022)
Video games are one of the industries that are growing very rapidly every year. And in a video game industry, there are many types/genres of games that have been widely circulated in the community. One of them is a type of game where players interact a little while the game is running, namely idle games. Even though gaming is one of the industries that is growing very rapidly, based on the report of Diana Paskarina (COO of game loka nutmeg) the contribution of the creative game industry is still very small to state revenue. However, regardless of the existing constraints, there are opportunities/opportunities that can be utilized to improve the country's economy through idle games. This refers to the results of the Sensor Tower survey which shows that the income of the idle game genre in Q3 2016 to Q2 2018 has increased very rapidly. Therefore, researchers try to make a positive contribution by developing game applications with the idle game genre using the Agile Game Development method.